Analisis Miskonsepsi Siswa pada Materi Asam Basa Menggunakan Two-Tier Multiple Choice di SMA Negeri 4 Gorontalo - Asmawati J. Salum; Mangara Sihaloho; Erni Mohamad (International Forum of Researchers and Lecturers, 2024)
This research aimed to identify students' misconceptions of acid-base material using a Two-Tier Multiple-Choice test at SMA Negeri 4 Gorontalo. It employed a qualitative descriptive approach, and the data collection techniques used were a Two-Tier Multiple Choice test instrument. Additionally, the research subjects were students in Class XI of SMA Negeri 04 Gorontalo, with a total sample size of 70.The research data were obtained from students' responses to the Two-Tier Multiple-Choice test questions.These responses were analyzed based on the students' answer patterns and categorized into three groups: Understood the Concept, Misconception, and Did not Understand the Concept The findings revealed that 10% of students understood the concept, 41% did not, and 49% had misconceptions. This result signified high misconception among studenst in Class XI of SMA Negeri 04 Gorontalo regarding acid-base material.